PENGARUH KECAKAPAN MANAJERIAL TERHADAP MANAJEMEN LABA DENGAN KUALITAS AUDITOR SEBAGAI VARIABEL PEMODERASI - Radityas Utami; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2013)
The objectives of this study is to examine the impact of managerial ability on earnings management. In addition, objective of this study is also to examine how the effect of audit quality in moderating the relationship between managerial ability and earnings management.The sample of the study is manufacturing companies listed on the Indonesia Stock Exchange in 2008 to 2010, with as many as 321 firms. Managerial ability is measured using Data Envelopment Analysis (DEA). Audit quality is measured using the user's perception of the quality of financial reporting by category Big 4 Firm and Non-Big 4. While earnings management is measured by the formula Jones modification.Using multiple regression analysis, it was found that managerial ability have positive impact to earnings management. However, the quality of the auditors did not moderate the relationship between earnings management and managerial skills.